(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Susanto AH, Dwiati M, Pratiwi S. 2020. Molecular characteristics of two phenotypically identical species of Asteraceae based on the intergenic spacer trnT(UGU)-trnL(UAA). Biodiversitas 21: 5164-5169. Ogiera (Eleutheranthera ruderalis) and nodeweed (Synedrella nodiflora) are two different weed species belonging to the family Asteraceae commonly found in tropical regions. At a glance, both species show highly identical morphology, thus leading to difficulty in distinguishing between them. Therefore, molecular data based on particular markers are required. Here, we use an intergenic spacer (IGS) in the cpDNA, i.e., trnT(UGU)-trnL(UAA), as the molecular marker to reveal the difference between the two species. A pair of PCR universal primers, i.e., B48557 as the forward primer and A49291 as the reverse primer, were employed to amplify the marker. Sequence alignment was performed by the use of ClustalW implemented in Bioedit version 7.0.4.1. The results revealed that some differences with respect to both indel and base substitution were observed. Overall, this led to longer IGS trnT(UGU)-trnL(UAA) sequences of E. ruderalis than those of S. nodiflora. Although no direct relationship between the genetic and phenotypic dissimilarities was proven, coincidence seemed likely to exist. This provides molecular evidence that the two phenotypically similar species are genetically different from each other.